Development of the first officially licensed live attenuated duck hepatitis A virus type 3 vaccine strain HB80 in China and its protective efficacy against DHAV-3 infection in ducks - Fu, Qiuling; Han, Xiangmin; Zhu, Chunhua; Jiao, Wenlong; Liu, Rongchang; Feng, Zhao; Huang, Yaping; Chen, Zhen; Wan, Chunhe; Lai, Zhi; Liang, Qizhang; Shi, Shaohua; et al. (Poultry science, 2024)
Duck hepatitis A virus type 3 (DHAV-3) is an infectious virus that is highly fatal to ducklings and causes significant economic losses in the duck industry worldwide. Biosecurity and vaccination are required to control the pathogen. In the present study, we attenuated a lowly pathogenic DHAV-3 clinical isolate, named as HB, by serial passaging in duck embryos, and followed by several adaptive proliferations in specific-pathogen-free (SPF) chicken embryos. The virulence of DHAV-3 at different passages was assessed by infecting 3-day-old ducklings. We found that the HB strain lost pathogenicity to ducklings from the 55th passage onwards. The 80th passage strain (HB80), which achieved good growth capacity in duck embryos with a viral titer of 108.17 50% egg lethal dose per milliliter (ELD50/mL), was selected as a live attenuated vaccine candidate. The HB80 strain did not induce clinical symptoms or pathological lesions in 3-day-old ducklings and showed no virulence reversion after 5 rounds of in vivo back-passage. The minimum effective dose of HB80 was determined to be 104.5 ELD50 by hypodermic inoculation of the neck. Importantly, a single dose of HB80 elicited good immune responses and provided complete protection against challenge with the lethal DHAV-3 strain. Compared with the genomic sequence of the parental HB strain, HB80 had 7 amino acid substitutions, two of them are in the hypervariable region of the VP1 and polymerase-encoding 3D regions, which may play a role in virulence attenuation. Our data suggest that the attenuated HB80 strain is a promising vaccine candidate for the prevention of DHAV-3 infections in China. HB80 has been registered as a New Veterinary Drug Registration Certificate by the Chinese Ministry of Agriculture and Rural Affairs (MARA), and is the first live attenuated DHAV-3 vaccine strain to be officially licensed in China.